The important role of CNS facilitation and inhibition for chronic pain. (December 2013) - Staud, Roland
Multiple studies have demonstrated that the pain experience among individuals is highly variable. Even under circumstances where the tissue injuries are similar, individual pain experiences may vary drastically. However, this individual difference in pain sensitivity is not only related to sensitivity of peripheral pain receptors, but also to variability in CNS pain processing. Peripheral impulses derived from tissue receptors undergo modification in dorsal horn neurons that can either result in inhibition or facilitation of pain. Such influences are particularly apparent in inflammation where not only peripheral, but also central, pain modulatory mechanisms can significantly increase nociceptive pain. Emotional state, level of anxiety, attention and distraction, memories, stress, fatigue and many other factors can either increase or reduce the pain experience. Increasing evidence suggests that 'bottom–up' and 'top–down' modulatory circuits within the spinal cord and brain play an important role in pain processing, which can profoundly affect the experience of pain.